Influence of Microstructure on Mechanical Properties of Bainitic Steels in Railway Applications - Omid Hajizad; Ankit Kumar; Zili Li; Roumen H. Petrov; Jilt Sietsma; Rolf Dollevoet (Metals, 2019)
Wheel−rail contact creates high stresses in both rails and wheels, which can lead to different damage, such as plastic deformation, wear and rolling contact fatigue (RCF). It is important to use high-quality steels that are resistant to these damages. Mechanical properties and failure of steels are determined by various microstructural features, such as grain size, phase fraction, as well as spatial distribution and morphology of these phases in the microstructure. To quantify the mechanical behavior of bainitic rail steels, uniaxial tensile experiments and hardness measurements were performed. In order to characterize the influence of microstructure on the mechanical behavior, various microscopy techniques, such as light optical microscopy (LOM), scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD), were used. Three bainitic grades industrially known as B360, B1400 plus and Cr-Bainitic together with commonly used R350HT pearlitic grade were studied. Influence of isothermal bainitic heat treatment on the microstructure and mechanical properties of the bainitic grades was investigated and compared with B360, B1400 plus, Cr-Bainitic and R350HT in as-received (AR) condition from the industry. The results show that the carbide-free bainitic steel (B360) after an isothermal heat treatment offers the best mechanical performance among these steels due to a very fine, carbide-free bainitic microstructure consisting of bainitic ferrite and retained austenite laths.